Towards integrated modeling of the long-term impacts of oil spills. (September 2021) - Solo-Gabriele, Helena M.; Fiddaman, Tom; Mauritzen, Cecilie; Ainsworth, Cameron; Abramson, David M.; Berenshtein, Igal; Chassignet, Eric P.; Chen, Shuyi S.; Conmy, Robyn N.; Court, Christa D.; Dewar, William K.; Farrington, John W.; et al.
Abstract: Although great progress has been made to advance the scientific understanding of oil spills, tools for integrated assessment modeling of the long-term impacts on ecosystems, socioeconomics and human health are lacking. The objective of this study was to develop a conceptual framework that could be used to answer stakeholder questions about oil spill impacts and to identify knowledge gaps and future integration priorities. The framework was initially separated into four knowledge domains (ocean environment, biological ecosystems, socioeconomics, and human health) whose interactions were explored by gathering stakeholder questions through public engagement, assimilating expert input about existing models, and consolidating information through a system dynamics approach. This synthesis resulted in a causal loop diagram from which the interconnectivity of the system could be visualized. Results of this analysis indicate that the system naturally separates into two tiers, ocean environment and biological ecosystems versus socioeconomics and human health. As a result, ocean environment and ecosystem models could be used to provide input to explore human health and socioeconomic variables in hypothetical scenarios. At decadal-plus time scales, the analysis emphasized that human domains influence the natural domains through changes in oil-spill related laws and regulations. Although data gaps were identified in all four model domains, the socioeconomics and human health domains are the least established. Considerable future work is needed to address research gaps and to create fully coupled quantitative integrative assessment models that can be used in strategic decision-making that will optimize recoveries from future large oil spills. Graphical Abstract: ga1 Highlights: A conceptual framework was developed for an integrated oil spill model that can be used to answer societal level questions. Framework includes four knowledge domains: ocean environment, biological ecosystems, socioeconomics, and human health. A causal loop diagram was developed to evaluate linkages and data gaps. System separates into two tiers, the natural systems and human systems. The largest knowledge gaps correspond to the socioeconomics and human health domains.